Pre-service Teachers' Knowledge Base at La Salle University - Anderson Cárdenas; Juan Manuel Suárez Osorio (Asociación Colombiana de Profesores de Ingles, 2009)
This paper reports on the outcomes of a recent study carried out at Universidad de La Salle, which intended to describe and reflect upon what five (5) pre-service teachers from last semesters pointed out as the most important elements of knowledge base that teachers should know in order to become English language teachers. The instruments utilized in this qualitative research to gather information from the participants were students' journals, a phenomenological interview and a survey. Results indicate that elements such as the language (English) command, students' preferences and realities, and the control of a class, among others, come to be essential areas teachers should be knowledgeable in.